PENGARUH FAKTOR LOKASI TERHADAP LABA USAHA TOKO BUAH DI KOTA BENGKULU - Luki Prasiska; Satria Putra Utama; Hariz Eko Wibowo; Emlan Fauzi (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2026)
Bengkulu City, as the capital of Bengkulu Province, has experienced rapid growth in the trade sector, in line with the increase in population reaching 397,321 people in 2024. This condition makes fruit shop businesses have great potential to develop, although their success is highly dependent on selecting a strategic location, considering that fruits are perishable goods. This study aims to map the distribution of fruit shop locations, analyze the influence of location factors on business profits, and formulate appropriate location selection strategies. The research was conducted from November to December 2025 using a census method of 35 fruit shops, of which 25 agreed to be interviewed. A descriptive quantitative approach was applied through GIS analysis and multiple linear regression. The results show that the distribution of fruit shops is uneven and concentrated in several districts, and that only the number of visitors significantly affects profits, indicating that location strategies must be adjusted to market characteristics.